Identification of Cooperative Learning Component in Designing Lesson Plan for Building Drawing Subject in Vocational Colleges - Mustaffa Kamal, Mohd Firdaus; Md Salleh, Raihanah; Mohd Zulkifli, Rafeizah; Mohd Jamil, Mohd Ridhuan; Othman, Haliza (Journal of Technical Education and Training, 2023)
Cooperative learning is a student-centered learning technique that can be considered a learning strategy for improving student performance both intellectually and in soft skill acquisition. Changes in curriculum structure in vocational institutions, because of the TVET transformation in 2012, have had an unforeseen influence on teaching and learning, whereas in the prior framework, a detailed teaching guideline was supplied compared to the latest structure. Teachers with inadequate knowledge and experience in learning strategies struggled to execute the new curriculum structure due to the lack of depth in these recent curriculum structure. This may be seen in the case of construction drawing subjects, where there were originally 14 main topics but now there are just four. Thus, the goal of this research is to help these teachers by offering a guideline for creating lesson plans that use a cooperative learning strategy. The aim of this paper is to identify and highlight the important component in the creation of a lesson plan using cooperative learning. For this investigation, the fuzzy Delphi technique was used. The main instrument for this study is a questionnaire survey that was developed utilizing a construct identified through literature and the results of a previous needs analysis. A total of 15 expert panels were chosen as the sample, which included university lecturers, vocational college instructors, officers from the Ministry of Education’s Technical and Vocational Training Division, and industry representatives. The data was analyzed with the help of Microsoft Excel FDM. Visual skills, Cooperative Student Team Achievement Division (STAD), Power Point, and demonstrations components have been recognized as the major component to include in the lesson plan based on the analysis. With these components identified, a good lesson plan guideline for the next phase of this study can be constructed. It is envisaged that the development of such guidelines would help to elevate the practice of teaching and learning to the next level.